Hydrogeochemical and Isotopic Characterisation of the Učja Aquifer, NW Slovenia - Petra Žvab Rožič (Geologija)
The groundwater characteristics of the Učja aquifer were investigated using geochemical and isotopic data. The water discharge and physico-chemical properties of the groundwater and the Učja River reflect the climate that is characteristic of the area. The mixed snow/rainfall regime is characteristic for the Učja Valley, with the highest discharges appearing during the spring snowmelt and autumn precipitation, and the lowest discharges in the winter and especially summer months. The temperature of the groundwater and the Učja River is lower in winter and higher in summer. The specific electrical conductivity values indicate a very permeable carbonate aquifer. Higher conductivity values were observed in spring and autumn at all sampling sites, which is related to snowy and rainy periods. The groundwater from the Učja aquifer indicates a uniform type of water (Ca-Mg-HCO3), with Ca2+, Mg2+ and HCO3– the most abundant ions. Differences in Ca2+ and Mg2+ concentrations and in the Mg2+/Ca2+ molar ratio between sampling sites were observed. Those springs with lower Mg2+ and lower Mg2+/Ca2+ molar ratios indicate limestone recharge areas, and those springs with higher Mg2+ and molar ratios indicate interaction with the dolomite hinterland. The pH values confirm alkaline waters characteristic of carbonate aquifers. The hydrogen (δ2H) and oxygen (δ18O) isotope values suggest the main source of water is from precipitation from a complex mixing of maritime and continental air masses. An altitude isotopic effect is observed with minor δ18O and δ2H depletion at higher altitude sampling sites compared to those springs at lower altitudes. The altitude isotopic effect is most prominent in spring. The δ13CDIC values indicate the dissolution of carbonates and the degradation of organic matter.